Impacto del potasio ajustado por PH en el desarrollo de hipopotasemia de pacientes con cetoacidosis diabética de un hospital nacional del Perú, 2021-2023 - Tuesta Suárez, Gladys Katerine (2025)
Potassium adjusted for pH in DKA focuses on the ability of pH-adjusted potassium to predict the timing and severity of hypokalemia in patients with diabetic ketoacidosis (DKA) during their treatment. The study proposes that the use of pH-adjusted potassium as a marker for hypokalemia could significantly improve both clinical outcomes and patient health by allowing a more appropriate initiation of potassium replacement. The main focus is the analysis of the impact of pH-adjusted potassium on the development of hypokalemia in patients with Diabetic Ketoacidosis (DKA) at the National Hospital of Loreto between 2021 and 2022. The aim is to evaluate the utility of serum potassium adjusted in the clinical management of hypokalemia, a common electrolyte disorder in patients with DKA. The methodology includes an observational, analytical, cross sectional, and retrospective study with a retrospective cohort design. It seeks to identify the clinical and sociodemographic characteristics of the patients, and to evaluate the association between hypokalemia and pH-adjusted potassium. This work is relevant to improve the understanding and management of hypokalemia in patients with DKA, using descriptive, bivariate, and multivariate analyses.